2021
DOI: 10.1016/j.rse.2021.112609
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling of far-red solar-induced chlorophyll fluorescence of different crops from canopy to leaf level using a diurnal data set acquired by the airborne imaging spectrometer HyPlant

Abstract: Remote sensing-based measurements of solar-induced chlorophyll fluorescence (SIF) are useful for assessing plant functioning at different spatial and temporal scales. SIF is the most direct measure of photosynthesis and is therefore considered important to advance capacity for the monitoring of gross primary production (GPP) while it has also been suggested that its yield facilitates the early detection of vegetation stress. However, due to the influence of different confounding effects, the apparent SIF signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…It is directly related to the photosynthetic apparatus of vegetation (Siegmann et al, 2021) and is sensitive to environmental stressors (Lee et al, 2013;Mohammed et al, 2019;Zeng et al, 2022;Zhang et al, 2014). With decreasing temperature, an increase in the fluorescence yield at both 685 nm and 735 nm is observed, and a marked change occurs at the longer emission, resulting in a decrease in the chlorophyll fluorescence ratio (Agati et al, 2000).…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is directly related to the photosynthetic apparatus of vegetation (Siegmann et al, 2021) and is sensitive to environmental stressors (Lee et al, 2013;Mohammed et al, 2019;Zeng et al, 2022;Zhang et al, 2014). With decreasing temperature, an increase in the fluorescence yield at both 685 nm and 735 nm is observed, and a marked change occurs at the longer emission, resulting in a decrease in the chlorophyll fluorescence ratio (Agati et al, 2000).…”
Section: Key Pointsmentioning
confidence: 99%
“…Solar‐induced chlorophyll fluorescence ( SIF ), a promising indicator, represents weak radiation at far‐red wavelengths (650–800 nm), which is reemitted by vegetation during the light reactions of photosynthesis (Wang, Clevers, et al., 2022; Zhang et al., 2018). It is directly related to the photosynthetic apparatus of vegetation (Siegmann et al., 2021) and is sensitive to environmental stressors (Lee et al., 2013; Mohammed et al., 2019; Zeng et al., 2022; Zhang et al., 2014). With decreasing temperature, an increase in the fluorescence yield at both 685 nm and 735 nm is observed, and a marked change occurs at the longer emission, resulting in a decrease in the chlorophyll fluorescence ratio (Agati et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of hyperspectral remote sensing has enabled the detection of many objects previously undetectable using broadband technology. The utilization of imaging spectrometers mounted on satellites enables various applications, such as ocean exploration [9,10], environmental monitoring, surface exploration [11], natural resources exploration [12], and biological activity monitoring [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that F and PRI measured from a variety of tower‐based (e.g., Cogliati et al., 2015; Kim et al., 2021; Wieneke et al., 2018; Xu et al., 2021), airborne (e.g., Middleton et al., 2017; Rascher et al., 2015; Rossini et al., 2015; Siegmann et al., 2021; Tagliabue et al., 2019), and spaceborne platforms (e.g., Middleton et al., 2016; Sun et al., 2018; Wang et al., 2020; Zhang et al., 2020) can successfully track variations in GPP and/or LUE . However, canopy‐scale F and PRI are not exclusively driven by plant physiology.…”
Section: Introductionmentioning
confidence: 99%